ANALISIS PERUBAHAN POLA OPERASI TERHADAP SUSUT TENAGA LISTRIK SISTEM DISTRIBUSI PLN ULP IMANDI - Aulia Sandhi Kurniawan; Adisastra Pengalaman Tarigan; Hamdani (CV. Hawari, 2025)
Losses are a natural phenomenon that cannot be avoided, because they are absolute and certain to occur in the distribution of electric power. Technical losses are influenced by the type of cross-section, cross-sectional area, natural factors such as temperature, and so on. In this study, the author analyzes changes in operating patterns against losses at PT PLN ULP Imandi with a spindle system or can be supplied from other feeders. In ULP Imandi there are 3 feeders, namely SO1, SLO7, and OB2, each of which is supplied from a different GI (main substation). The purpose of this study is to analyze the technical losses that occur in ULP Imandi so that a value is obtained with the help of ETAP software which can then be used as a reference for evaluation. ULP Imandi has a feeder length of 207.22 kms with a AAAC 50mm2 cross-section of 60.093 kms, AAAC 95 mm2 of 84.273 kms, and AAACS 150 mm2 of 62.854 kms. With this data, the ideal loss value for ULP Imandi is 119,448 kWh/month.